PERLINDUNGAN HUKUM DALAM MENYAMPAIKAN PENDAPAT DIMUKA UMUM DI TENGAH PANDEMI COVID-19 DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Gheantoro, Fadil (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Covid-19 that attacked Indonesia in early 2020, the pandemic that occurred has robbed many of the people’s rights, many people have also been unable to carry out their activities as usual. Starting from work, school, playing, to demonstrations / expressing opinions in public places. Large-Scale Social Restrictions or PSBB is one of the government’s many efforts to overcome the Covid-19 virus by limiting the activities of residents who are considered to have the potential to spread Covid-19. PSBB has affected many things, starting from school activities, the economy and democracy in terms of expressing opinions in public or demonstrations. Even though demonstrations / expressions of opinion in public places have actually been protected and stated in the 1945 Constitution in article 28F "Everyone has the right to communicate and obtain information to develop his personality and social environment, and has the right to seek, obtain, possess, store, process, and convey information using all types of available channels", then in Law Number 39 of 1999 which discusses Human Rights Article 25 "Every person has the right to express opinions in public, including the right to strike in accordance with the provisions of the law - invitation” and also in Law Number 9 of 1998 concerning Freedom of Expressing Opinions in Public.